2022
DOI: 10.3390/w14182771
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Quality Assessment of Greek Lowland Rivers with Aquatic Macrophytes in Compliance with the EU Water Framework Directive

Abstract: Aquatic macrophytes are one of the four biological quality elements (BQE) used for assessing the ecological status of inland waters according to the EU Water Framework Directive (WFD 2000/60). With this article, we present the methodological approach for the implementation of a WFD compliant macrophyte index to the riverine systems of Greece. In addition to the definition and harmonization of the ecological quality class boundaries, the results from the pilot application of the index and the ecological classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Studies of hydromorphological alterations in rivers and/or their impacts on biodiversity are numerous [33][34][35][36][37][38]; however, few papers explicitly deal with HMWBs and AWBs and use adapted assessment methodologies (e.g., [39]). For example, the Polish hydromorphological assessment methodology presented in Garbowski et al [23] does have lower score thresholds for AWBs, but it does not determine MEP or take into consideration mitigation measures, as we did in this study.…”
Section: Challenges In Assessing Hydromorphological Conditions Of Hmw...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hydromorphological alterations in rivers and/or their impacts on biodiversity are numerous [33][34][35][36][37][38]; however, few papers explicitly deal with HMWBs and AWBs and use adapted assessment methodologies (e.g., [39]). For example, the Polish hydromorphological assessment methodology presented in Garbowski et al [23] does have lower score thresholds for AWBs, but it does not determine MEP or take into consideration mitigation measures, as we did in this study.…”
Section: Challenges In Assessing Hydromorphological Conditions Of Hmw...mentioning
confidence: 99%
“…To obtain a complete picture of ecosystem function and distinction of MEP sites, the results of this study should be combined with the results of biological monitoring in order to determine the response of biological communities at different levels of degradation [36,37]. In Croatia, a study on hydromorphological alterations of natural water bodies [54] showed that homogenization of the substrate is especially problematic for invertebrates.…”
Section: Impact Of Hydromorphological Modifications On Biological Qua...mentioning
confidence: 99%
“…Hydromorphological features (e.g. type of channel substrate, effects of hydrological and morphological modifications, bed stability, channel shade) were assessed during the plant sampling according to Stefanidis et al (2022). A description of the environmental variables that were considered in this study is listed in Table 1.…”
Section: Environmental Parametersmentioning
confidence: 99%
“…A description of the environmental variables that were considered in this study is listed in Table 1. For further details on field samplings, characteristics of river reaches, macrophyte identification and quantification of physicochemical and geomorphological variables see our publications (Stefanidis et al, 2021;Papastergiadou, 2022;Stefanidis et al, 2022).…”
Section: Environmental Parametersmentioning
confidence: 99%
See 1 more Smart Citation